Emphasizing the Science, Technology, Engineering, and Math (STEM) in Agricultural Extension - Kathryn A. Stofer; Laura A. Warner; Steven Arthurs (EDIS)
STEM is an acronym for science, technology, engineering, and math. In Extension, our purpose is to share the knowledge or products created through Ag-STEM research and design by universities and government agencies. Finding effective solutions to agricultural issues, especially in urban areas, increasingly involves working with clientele to solve problems jointly. Therefore, emphasizing the connections of STEM to agricultural problems through Ag-Extension programming can help our public audiences comprehend the problem-solving system underlying the content. The goal is to provide public audiences with self-confidence and skills in STEM, preparing them to be more engaged in the problem-solving process for the challenges ahead. This 5-page fact sheet was written by Kathryn A. Stofer, Laura A. Warner, and Steven Arthurs, and published by the UF Department of Agricultural Education and Communication, October 2014. (UF/IFAS photo by Tyler Jones.)